2022
DOI: 10.56572/gjoee.2022.si.0012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cluster Frontline Demonstration Towards Transfer of Scientific Cultivation Practices of Major Pulses in Navsari District of Gujarat

Abstract: The cluster frontline demonstrations (CFLDs) on pigeon pea, chick pea and summer green gram were conducted by Krishi Vigyan Kendra, Navsari. Gujarat during the year 2018-19 in three talukas of Navsari district, i.e., Chikhli, Khergam and Vansda. Total 577 demonstrations on pigeon pea, chickpea and summer green gram pulse crops were carried out in an area of 82 ha by the active participation of farmers with the objective to demonstrate the scientific cultivation practices of major pulses. The scientific cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
2
0
0
Order By: Relevance
“…The other reasons include dissimilarity in soil fertility status, agricultural practices and local climatic situation. This finding is supported by Ajrawat et al (2013), Singh et al (2014), Romade et al (2018) and Shah et al (2019).…”
Section: Methodssupporting
confidence: 58%
“…The other reasons include dissimilarity in soil fertility status, agricultural practices and local climatic situation. This finding is supported by Ajrawat et al (2013), Singh et al (2014), Romade et al (2018) and Shah et al (2019).…”
Section: Methodssupporting
confidence: 58%
“…In comparison to the farmers' practice, there was an increase of 29.8, 35 and 36.9 percent in productivity of rice crop under the recommended practice in the year 2018.2019 and 2020 respectively. Similar type of results in increase the yield of Rabi onion FLDs was reported by Arora et al (2014), in cumin FLDs was found by Sondarva, et al, (2014)., in paddy FLDs was reported by Dhenge et al(2014) and Shah et al(2019) reported increase in the yield of major pulse FLDs plots.…”
Section: Crop Yieldsupporting
confidence: 61%